Wpływ przystąpienia do Unii Europejskiej na międzynarodową współpracę policyjną Polski - Szumski, Adrian (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2014)
Accession to the EU caused essential changes in Poland’s international police cooperation. Thus Poland is able to impact the EU policy in that respect and to expands possibilities of its own international policy implementation. Preeminently these changes are being reflected in participation of the Polish police in international missions carried out under the auspices of the EU, which aim at strengthening stability of particular state that experience a conflict or states that are in conflict with another subject.
Keywords: oficerowie łącznikowi; operacje pokojowe; policja; Unia Europejska; współpraca policyjna